Editoriale - Francesca Tosi (And, 2020)
The Italian university educational offer in Design - articulated in the three-year degree courses in "Industrial Design" and in the master's degree courses in "Design" - has experienced in recent years a very strong development parallel to the expansion of the role and areas of intervention of Design - and of designers - within the productive and social system and, on the other hand, to the recognition of the role of Design as a driver and strategic factor of innovation.